Teachers’ Perceptions of the Effectiveness of Internal School Quality Assurance Implementation in Enhancing Primary School Leadership in Dodoma Urban - Daniel, Charles Shoide; Biswalo, Upendo (Journal of Education and Practice, 2025)
Purpose: The purpose of this study was to explore teachers’ perceptions of the effectiveness of ISQA implementation in enhancing primary school leadership in Dodoma Urban, Tanzania. The study was anchored in Scientific Management Theory, which underscores systematic organization, accountability, and efficiency, and Human Relations Theory, which stresses motivation, collaboration, and teacher engagement. Methodology: The study adopted a qualitative phenomenological design. A total of 18 participants, including teachers and headteachers, were purposively selected from six schools to provide insights based on their engagement with ISQA activities. Data were collected through in-depth interviews and were analyzed thematically. Findings: The findings revealed that ISQA contributed to improved teacher involvement in decision-making, enhanced instructional supervision, better time management, and increased accountability. However, challenges such as a lack of training, inconsistent implementation, and limited administrative support hindered its full effectiveness. Unique Contribution to Theory, Policy and Practice: The study concludes that while ISQA holds significant potential for strengthening school leadership, its success depends on consistent support, clear guidelines, and adequate capacity-building. It recommends targeted training, provision of resources, and inclusive teacher participation in ISQA practices to ensure sustainable leadership development and improved school performance.